Challenges and Technology Trends in Implementing a Human Resource Management System: A Systematic Literature Review - Destriani, Rahma; Adhitama, Raihansyah Yoga; Sensuse, Dana Indra; Hidayat, Deden Sumirat; Purwaningsih, Erisva Hakiki (Universitas Airlangga, 2024)
Background: Human Resource Management System (HRMS) is an important aspect of managing organizations. However, the successful integration of the system into respective roles is often associated with diverse technological challenges and trends. Some major obstacles identified in recent research include reluctance to change, lack of training, fragmented Human Resource (HR) data, rigid processes, and continuous changes in organizational needs. Exciting technology trends offer promise for next-generation HRMS solutions, including artificial intelligence (AI), machine learning, predictive analytics, and mobile accessibility. This shows the need for a systematic literature review to comprehensively map the challenges and technology trends shaping the implementation of HRMS. Objective: This research aimed to conduct a comprehensive review of existing literature to identify the main challenges faced during HRMS implementation and the latest technology trends in the space. Methods: A systematic literature review was adopted through the Kitchenham method with a focus on five databases including Scopus, Emerald, IEEE, Science Direct, and ProQuest. Results: The result was in the form of a table mapping of the challenges faced by each stakeholder in HRMS, including resistance to change, lack of management support, and limited technology infrastructure. Meanwhile, the most common technology challenges found were system integration issues, data security, and lack of technical capabilities or skills. The potential opportunities from technology trends to address the issues included training and skills development, enhanced cybersecurity, and effective change management methods. These recommendations were designed to support organizations in further optimizing HRMS utilization and leveraging the latest technologies such as AI and blockchain. Conclusion: The review used a structured method to develop a rich overview through tabular presentations summarizing problem identification and technology trend compilation of HRMS. The systematic exploration aimed to contribute valuable insights into the complexities of HRMS implementation and offer a comprehensive perspective on the emergence of relevant technology trends. The results were expected to contribute to future research directions in this important area at the nexus of Human Resource Management (HRM) and technological innovation. Keywords: Human Resource Management System, Challenges, Technology Trends, Systematic Literature Review